Financial management decisions : principles and applications - Stewart, Alison.; Gregory, Warwick.; Lumby, Stephen.; Hutchinson, Patrick. (Thomas Nelson, 1994)
This book is divided into two parts: Principles; Applications of Financial management decisions.